Autoethnography as a method of facilitating critical reflexivity for professional doctorate students - Catherine Hayes (Association for Learning Development in Higher Education (ALDinHE), 2015)
This paper explores autoethnography within the context of the professional doctorate and argues that it is an excellent way of linking theory to the practical situation. The paper commences by defining the Ã¢â¬Ësecond generationÃ¢â¬â¢ of professional doctorates (Maxwell, 2003) where the focus is directed primarily to work-based learning and the development of work-based practice. Candidates are expected to demonstrate the development of practice and their contribution to this in a fundamentally original approach. The researcher is central in the practical or work-based situation and the process of autoethnography can structure and guide the research process, by providing structure to the process of reflexivity. The paper considers two broad approaches to autoethnography: the traditional approach and the post-modernist approach. The post-modernist approach presents challenges in the ways in which the work is presented: a central argument of the paper is that despite the novel ways of presentation, the work should have a strong theoretical base. The paper concludes by summarising the role of autoethnography in the professional doctorate: autoethnography provides a factually accurate and comprehensive overview of the professional doctorate candidateÃ¢â¬â¢s career trajectory. It should act as a driver of self-explication for the professional doctorate student thus providing a degree of both catalytic and educative authenticity, and provide an insight for the reader of the professional doctoral thesis.